Porcupine, Picayune, & Post how newspapers get their names - Bernhard, Jim.; ebrary, Inc. (Columbia : University of Missouri Press, 2007)
"Porcupine, Picayune, & Post examines the history and etymology of newspapers' names. Bernhard focuses on printed general-interest English-language dailies and weeklies, from the Choteau (Montana) Acantha to the Moab (Utah) Zephyr, with everything in between"--Provided by publisher.
Includes bibliographical references (p. 183-187) and indexes.
Electronic reproduction.
Keywords: Titles of newspapers -- Great Britain; Titles of newspapers -- United States; Electronic books